Flypaper Effect: The Shifting Unconditional Transfer and Private Income in Indonesia - Sherlita Nurosidah; Mohamad Khusaini; Ferry Prasetyia (Journal of International Conference Proceedings, 2022)
This study aims to analyze the behavioral pattern of local government as seen from their spending regarding unconditional transfer and private income. Flypaper effect has been a major phenomenon in academic research. Nevertheless, in Indonesia, such research, especially the one focusing on the shift of unconditional transfer and private income, never been caried out. Over 22 years, Indonesia has been implementing decentralization which makes it more intriguing to see local governments’ budget and spending decisions’ motives. This paper uses a panel data from 476 districts and cities in Indonesia for 11 years. Classical assumption tests, endogeneity test as well as instrumental validation test were caried out before doing the regression. The result from two-stage least square regression shows that flypaper effect does not present in total spending yet appears in four other kinds of spending. Asymmetric response of those five are quite varied. Total expenditure and capital expenditure have symmetrical response. Meanwhile, operational spending and transfer spending have a fiscal replacement type of asymmetry. On the other hand, unexpected spending shows a fiscal restraint asymmetry. The direction of private income’s influence to spending also seen to be different from one another.